Introducing the IBM DS8882F Rack Mounted Storage System - Manthorpe, Stephen; Brunson, Sherry; Dufrasne, Bert (IBM Redbooks, 2018)
This IBM® Redpaper™ presents and positions the DS8882F. The DS8882F adds a modular rack-mountable enterprise storage system to the DS8880 family of all-flash enterprise storage systems. The modular system can be integrated into 16U contiguous space of an existing IBM z14™ Model ZR1 (z14 Model ZR1), IBM LinuxONE™ Rockhopper II (z14 Model LR1), or other standard 19-inch wide rack. The DS8882F allows you to take advantage of the performance boost of DS8880 all-flash enterprise systems and advanced features while limiting datacenter footprint and power infrastructure requirements.